Farmer perceptions of climate change and adaptation during the 2017–2020 Australian drought. Issue 4 (2nd October 2022) - Miller, Gabrielle; MacNeil, Robert
ABSTRACT: Despite being the most tangibly impacted by the first-order effects of a warming climate, much of Australia's agricultural regions have remained relatively conservative in their views on climate change and the need for adaptation. This paper aims to understand how the experience of an extreme climate event like the 2017–2020 drought might shift opinions and values on these issues within agricultural communities. Through in-depth interviews with 20 graziers across Northwest NSW during the worst days of the drought, we found that various psychological lock-ins, historical memories of resilience, and local cultural values appeared to be undermining the perception of their vulnerability, while enhancing perceptions of their ability to endure. Such discursive constructions appear to explain why a jarring climatic event like the 2017–2020 drought was failing to produce a noticeable shift in their views.